2003
DOI: 10.1136/vr.153.18.549
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors that may predispose domestic cats to road traffic accidents: part 1

Abstract: Between March 2000 and February 2001, six veterinary practices in Cambridgeshire collected data on 117 owned cats which they had examined after a road accident. For one week every month during the same year, the practices distributed questionnaires to the owners of cats which had been examined for reasons other than a road accident, and the data from these cats were checked to ensure that they were representative of the practice records, which were compared with a survey of the owned cat population for age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
80
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 7 publications
9
80
2
1
Order By: Relevance
“…This compares with just 5.8% of trauma-related deaths in cats dying at or after 5 years of age. The preponderance for RTA-related deaths among younger cats concurs with a UK practice-based study that reported reducing RTA death rates as cats aged (29). A Swedish study of insured cats that died before 12 years of age also identified RTA as important to cat mortality, with an age-standardised mortality rate (ASMR) of 411 per 10,000 cat-years at risk (17).…”
Section: Discussionsupporting
confidence: 49%
“…This compares with just 5.8% of trauma-related deaths in cats dying at or after 5 years of age. The preponderance for RTA-related deaths among younger cats concurs with a UK practice-based study that reported reducing RTA death rates as cats aged (29). A Swedish study of insured cats that died before 12 years of age also identified RTA as important to cat mortality, with an age-standardised mortality rate (ASMR) of 411 per 10,000 cat-years at risk (17).…”
Section: Discussionsupporting
confidence: 49%
“…Younger cats of around six months of age are more likely to be exposed to roads for the first time as owners will tend to keep kittens indoors until they have been neutered, which is often at around six months of age (Welsh and others 2013). This may explain the finding by Rochlitz (2003a).…”
mentioning
confidence: 69%
“…For example, it has been suggested that black cats are more likely to be involved in an RTA due to being less visible to drivers. However, previous studies have not found any conclusive evidence to support this claim (Rochlitz 2003a). In addition, some animal rescue organisations will not rehome cats to houses situated on busy roads or will recommend that cats are kept indoors at night to reduce the risk of an RTA (eg Wythall Animal Sanctuary 2013, Leeds Cat Rescue 2014, RSPCA Stafford, Wolverhampton & District Branch 2014, Cheltenham Animal Shelter 2015).…”
mentioning
confidence: 83%
“…Tarsal injuries in male cats are overrepresented compared to female cats; tomcats have a wide home range and roam in search of oestrus females (Owen 2000, Rochlitz 2003). Complete physical and orthopaedic examinations are mandatory to reliably identify all injuries in these cases, but the recognition and management of all life-threatening injuries must take precedence over orthopaedic trauma.…”
Section: Patient Evaluationmentioning
confidence: 99%